Developing an Architectural Model for Social Health Networks and the Possible Risks of its Implementation in Shariati Hospital - Atefeh Sadat Haghighat Hoseini; Hossein Bobarshad; Fatemeh Saghafi; Iman Noroozi (Tehran University of Medical Sciences, 2018)
Background and Aim: The emergence of Web interactive technologies has enabled interactive social networking services. The purpose of this research is to choose a model and present an architectural design for the social network of health at Shariati Hospital in Tehran. Materials and Methods: At first, valid enterprise architecture frameworks were reviewed. Then, dimensions of the architecture frameworks needed for the social network of health were reviewed and six dimensions including of input, output, goals, views, abstraction, and system life cycle were selected. Architecture frameworks were prioritized on the basis of these six dimensions and the Zachman framework was selected. The extracted elements for these dimensions were evaluated by using a researcher-made questionnaire and experts' opinion in the t-test. The questionnaire was distributed among 40 health-care information technology experts. After analyzing and verifying the dimensions and sub-indicators of each dimension, probable risks for the implementation of the health social network were identified based on interviews with experts and were approved by a panel of five experts. Results: The Zachman framework was selected based on six dimensions as a suitable framework and potential implementation risks were identified. Conclusion: The results showed that the proposed architecture model could be the basis for the implementation of this network in the country. Attention to extracted risks can minimize the failure of the implementation of the health social network.